دور الدراسات الائتمانية الكافية في الحد من مخاطر الائتمان دراسة ميدانية على المصارف التجارية الليبية - الفرجاني إبراهيم مسعود (Scientific Journal of University of Benghazi, 2021)
The aims of the study are to identify the role of adequate credit studies in reducing credit risks in Libyan commercial banks, and to achieve the goal of the study, the descriptive analytical approach has been used. The study population consisted of the largest six Libyan commercial banks in terms of the volume of credit granted; which are Al Wahda Bank, Jumhouria Bank, Sahara Bank, National Commercial Bank, Bank of commerce and Development, and North African Bank. A questionnaire was used for collecting data which are used in testing study's hypotheses (84) questionnaires forms were received out of (90) distributed, including (2) forms that are not valid for statistical analysis, there for the number of forms included in the analysis are (82) forms, and the SPSS software was used to test the data statistical. The study concluded that credit committees and credit officers (study sample) have experience, competence and scientific qualification in the field of bank credit; in addition to that, there is a role for adequate credit studies in reducing credit risks.Based on the finding, the study recommended a set of recommendations; one of them is the need to expand credit studies to ensure credit risk reduction.